Modeling and Performance Analysis of the IEEE 802.11 MAC for VANETs under Capture Effect - Shah, A. F. M. Shahen; Ilhan, Haci; Tureli, Ufuk (IEEE, 2019)
Vehicular ad hoc networks (VANETs) have recently attracted interest for automation and intelligent transportation system (ITS). Channel capture influences the performance of VANETs in practical transmission. In this paper, to assess the performance of the IEEE 802.11 medium access control ( MAC) for VANETs under capture effect, an analytical model based on Markov chain model is presented. The parameters that could impact performance are studied. The relationship among parameters and performance metrics are derived. The probability of successful transmission, probability of frame capture, and throughput expressions are obtained. Furthermore, to verify the analytical studies numerical results are presented.
Keywords: Capture; IEEE 802.11; MAC; Markov chain model; VANETs; DCF; Computer Science; Engineering; Telecommunications